DIFFERENCES OF CATCHING BAMBOO BUBU AND WIRE BUBU AT THE OMBILIN RIVER, SAWAHLUNTO CITY WEST SUMATRA PROVINCE - Astri Rahmahdani; Polaris Nasution; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACThe dominant fishing gear used in the Ombilin River is the bamboo trap compared to other fishing gear. The process of making bamboo traps takes a long time and the type of bamboo used as the basic material for the bubu is increasingly difficult to obtain, so some fishermen try to use PVC wire counters. This study aims to compare the number of catches using bamboo traps and wire traps operated in the Ombilin River. The results showed that the difference in the number of catches based on weight and tail was more wire traps than bamboo traps. The number of catches based on tails and weight obtained by bamboo traps with an average catch for 15 days of capture is 37.33 fish (2533.20 grams), while in wire traps the average catch is 52.86 fish (2810.87 grams). Keywords : bamboo trap, wire trap, number of catches.